Utility of radiotherapy for treatment of basal cell carcinoma: a review. (1st November 2014) - Cho, M.; Gordon, L.; Rembielak, A.; Woo, T.C.S.
Summary: Radiotherapy is an available treatment for management of basal cell carcinoma (BCC). This study aims to analyse the published literature about radiotherapy in treatment of BCC. A focus of this study will be to compare the dosing regimens adopted in these studies. A search of the Medline database was conducted from 1984 to August 2013. Search terms used were 'basal cell carcinoma', 'radiotherapy', 'epithelial skin cancer' and 'external irradiation'. Fourteen studies on the use of radiotherapy for BCC were included. Seven studies included only cases of BCC, while six studies also included patients treated for squamous cell carcinoma. The overall cure rates ranged from 79·2% to 100%. More than 90% of the patients reported good or excellent aesthetic outcome from radiotherapy (three studies). There was a wide variation in the total dose and dose per fraction of radiotherapy used. Nine studies utilized dosing regimens within the recommended guidelines of the National Comprehensive Cancer Network. There are a limited number of high‐quality prospective studies of radiotherapy for BCC. Based on the available evidence, radiotherapy provides a high rate of local control with low rates of complications that are comparable with surgery.